Proceso atención de enfermería en adulto mayor con hipertensión arterial y diabetes mellitus tipo 2. - Bastidas Arambulo, Susy Carolina (2022)
The case study presented below focuses on the nursing care process of a 74-year-old patient with high blood pressure and diabetes mellitus, who attends the "By Pass" sub-center as an outpatient for monthly check-ups. During the nursing evaluation of the patient, facial pallor, diaphoresis, no edema, he reported not having eaten breakfast and his limited ambulation assisted with a cane. Arterial hypertension is a disorder of the blood vessels in which excessive pressure on the artery wall, arising from a systolic pressure equal to or greater than 140 mm Hg and/or a diastolic pressure equal to or greater than 90 mm Hg, respectively, meanwhile, type 2 diabetes mellitus is a serious disease that affects Ecuador and occupies the third place as causes of death in the country, where its main definer is the inability of the body to metabolize glucose, an indicator that encourages the population to better quality nutrition and disease prevention. Nursing care and its application includes definition, etiology, diagnosis of complications and treatment of disease developed according to the functional and taxonomic models of Marjorie Gordon through NANDA (diagnosis), NIC (intervention) and NOC (result); the management of nursing activities is planned, high blood pressure and type 2 diabetes depend on providing scientific evidence to achieve a healthy recovery in the patient.